VALIDITY OF ELECTRONIC POCKETBOOK CONTAINING DIVERSITY OF ANURA IN TANIPAH, SOUTH KALIMANTAN - Ririn Hidayat; Mahrudin Mahrudin; Riya Irianti (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Study of Anura can be used as material for enriching learning resources in school, as well as being a material for developing local potential, development is carried out in the form of an electronic pocket book. One of biology subject matter that can be applied with local potential is biodiversity. The purpose of this study was to describe validity of electronic pocket book containing study of Anura diversity in Tanipah, South Kalimantan. This book has been prepared as additional reading material on biodiversity. This development research use Borg and Gall model, but only on step (1) research and data collection, (2) planning, (3) initial product development, (4) initial field trial, and (5) major revision. Data collection is carried out directly in the field, then the data is integrated to electronic pocket book. The result of pocket book validity test is 94%, mean very valid. Based on the assessment, the book can be used as material for enriching concept of biodiversity.